2020
DOI: 10.1186/s12888-020-2477-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of restricted/repetitive behavior in autism spectrum disorder:a systematic review and meta-analysis

Abstract: Background: This paper is a systematic review and meta-analysis of the efficacy of available medications for the treatment of restricted/repetitive behavior (RRBs) in Autism Spectrum Disorder (ASD). Method: We searched MEDLINE, Embase, PsycINFO, The Cochrane Library (Cochrane Database of Systematic Reviews (CDRS), the Cochrane Central Register of Controlled Trials (CENTRAL), database of Abstracts of Reviews of Effects (DARE)), Scopus, Epistimonikos, Clinicaltrials.gov, and included all randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
0
30
0
1
Order By: Relevance
“…Nevertheless, the observations regarding the general dysfunction of the reward circuitry in individuals with ASD [13], along with the positive results of OXT administration in murine models [28,29], prompted the use of OXT as a therapeutic means in individuals with ASD. While some trials showed a promising beneficial effect of OXT on social behavior via modulation of the reward pathway [33][34][35], several meta-analyses failed to demonstrate a clear-cut benefit of OXT over placebo in alleviating autistic core symptoms [36][37][38].…”
Section: Oxytocinmentioning
confidence: 99%
“…Nevertheless, the observations regarding the general dysfunction of the reward circuitry in individuals with ASD [13], along with the positive results of OXT administration in murine models [28,29], prompted the use of OXT as a therapeutic means in individuals with ASD. While some trials showed a promising beneficial effect of OXT on social behavior via modulation of the reward pathway [33][34][35], several meta-analyses failed to demonstrate a clear-cut benefit of OXT over placebo in alleviating autistic core symptoms [36][37][38].…”
Section: Oxytocinmentioning
confidence: 99%
“…Additionally, the benefits of pharmacological medications in improving ASD behavior are highly variable across studies and clinical populations. There is also a paucity of long-term clinical trials with a large sample size on pharmacological interventions against restricted/repetitive behavior in ASD (Yu et al, 2020 ; Zhou et al, 2020 ). Furthermore, there is a lack of evidence-based treatment strategies targeting diverse repetitive/restricted behaviors in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…However, health regulatory authorities like the US Food and Drug Administration (FDA) have approved some pharmacological and nonpharmacological management options that aim to alleviate some of the signs and symptoms that could be associated with ASDs [14,15]. Today, prescription of pharmacotherapeutic options to manage and alleviate behavioral symptoms of ASDs like tantrums, aggressiveness, hyperactivity, and anxiety is increasingly popular in clinical practice [14][15][16][17]. Analysis of medication prescription has shown increasing volumes of psychoactive drugs among individuals with ASDs [17,18].…”
Section: Introductionmentioning
confidence: 99%